The Impact of Paraspinal Muscle Changes on Back Pain After Single-Segment Posterior Lumbar Laminectomy - Baek, Sung-Nyun; Kim, Young-Jae; Kim, Min-Seok; Choi, Yong-Soo (Journal of Korean Society of Spine Surgery, 2024)
Study Design: Retrospective study. Objectives: This study analyzed the impact of paraspinal muscle changes after single-segment posterior lumbar laminectomy. Summary of Literature Review: Posterior laminectomy of the lumbar spine requires significant manipulation of the paraspinal muscles, such as muscle detachment and retraction, all of which have been associated with low back pain. Materials & Methods: Thirty-three patients who had preoperative clinical records, lumbar lateral radiographs, and lumbar magnetic resonance imaging (MRI) and were available for final follow-up were enrolled. The lumbar extensor muscle was delineated using a pseudo-coloring technique in the vertebra where laminectomy was performed. Degeneration of the facet joints on MRI was classified according to the Weishaupt grading system. Changes in lumbar extensor muscles and facet joint degeneration, radiological parameters, and clinical outcomes were analyzed. Results: At the final follow-up, the muscle ratio of the lumbar extensors was 56.4±11.2%, which was lower than the preoperative muscle ratio of 70.4±12.0% (p<0.01). Final follow-up MRI showed that the degenerative changes in the facet joints were aggravated at the laminectomy site (p<0.01). At the final follow-up, loss of lumbar extensors and facet joint degeneration were associated with low back pain (lumbar extensors; r=0.80, p<0.01; facet degeneration; r=-0.66, p<0.01, respectively). Conclusions: The loss of the extensor muscles and degenerative changes of the facet joint in the index segment after posterior laminectomy could be associated with low back pain. KCI Citation Count: 0